Memory, Place, and Mobility: Kinchela Boys Home Aboriginal Corporation's Mobile Education Centre as a Site of Conscience. Issue 2 (May 2022) - ,; McComsey, Tiffany; Porter, Amanda
This "postcard" examines the development of Kinchela Boys Home Aboriginal Corporation's (KBHAC) Mobile Education Centre as a mobile "site of conscience" as well as a place of Indigenous resistance and truth-telling in White Australia. KBHAC's Mobile Education Centre is a whole of community experiential learning facility and aims to educate children, young people, and communities (Aboriginal and non-Indigenous) through three levels of engagement drawing on a range of resources: oral testimony, archival footage and artifacts, animated film, visual images, and interactive materials including an online portal. The Mobile Education Centre represents one example of decades of advocacy of survivors to raise awareness about Kinchela Boys Home and the experiences of Stolen Generations survivors. This postcard tells the story of KBHAC's Mobile Education Centre and situates it within the context of ongoing efforts to reclaim the former Kinchela Boys Home site, located on Dunghutti Country, Mid-North Coast, New South Wales. In doing so, this article seeks to document the story of a mobile site of conscience which seeks to educate about past harms and the intergenerational impacts of genocidal laws and policies while creating a space for truth-telling that supports the process of post-traumatic growth and intergenerational healing.